Methodological report: The appropriate scaling of weightlifting performance - Challis, J. H. (The Journal of Strength and Conditioning Research, 1999)
Based on isometric scaling principles, a relationship was derived that states that the mass a subject can lift is proportional to body mass2/3. This study examined the validity of this relationship by fitting it to the world lifting records from different mass classes. The exponent was 0.64 for Olympic lifting and 0.65 for power lifting, giving a good match to the theory. The derived relationship was then used to examine the scaling of weightlifting performance. Weightlifting data were scaled by the Schwartz formula, and also by dividing total mass lifted by either subject mass or by subject mass2/3 (isometric scaling). The isometric scaling method was the most appropriate as it varied the least across mass classes. It is proposed that scaling based on isometric principles should be used if interindividual or intergroup weightlifting performances are to be compared.